Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/su151310487
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Sustainability Vision for the Global Wine Industry

Moritz Wagner,
Peter Stanbury,
Tabea Dietrich
et al.

Abstract: Interest in sustainability has increased significantly in the wine sector in the past few years, driven by customer interest, as well as the impact of global warming-intensified weather extremes on wine growers. For a sustainable future the wine industry must design its entire value chain in such ways that it conserves and regenerates the natural environment and at the same time promotes human rights, inclusion and equality. The current paper identified five key challenges which have to be overcome in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 167 publications
1
7
0
Order By: Relevance
“…This integration is in line with the existing literature that emphasizes the symbiotic relationship between B.I. and S.F., enhancing organizations' decision-making capabilities in complex and uncertain environments [39,46,50,53]. The seamless integration of B.I.…”
Section: Impact Of Business Intelligence On Strategic Foresightsupporting
confidence: 85%
See 2 more Smart Citations
“…This integration is in line with the existing literature that emphasizes the symbiotic relationship between B.I. and S.F., enhancing organizations' decision-making capabilities in complex and uncertain environments [39,46,50,53]. The seamless integration of B.I.…”
Section: Impact Of Business Intelligence On Strategic Foresightsupporting
confidence: 85%
“…The research results indicated that B.I. systems provide a framework for utilizing data to support decision-making in unpredictable environments, which enhances the building of future scenarios [46,53,54]. Furthermore, companies must cultivate foresight in comparison to their rivals and proactively respond based on insights and alerts to ensure their survival and ongoing operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change is a threat to grapevine growers and the wine industry. Indeed, a variety of bioclimatic indices have been developed in order to scrutinize productivity in the field, accompanied by possible adaptation strategies [50][51][52][53][54][55][56][57][58][59][60]. At the winemaking level, the proposed strategies include chemical and microbiological acidification [61].…”
Section: Discussionmentioning
confidence: 99%
“…The wine sector is also an important driver of the rural economy, providing income and employment opportunities for many farmers and wineries, especially in marginal and less-favoured areas [42,44]. Moreover, the wine sector contributes to the provision of various ecosystem services, such as biodiversity conservation, soil protection, carbon sequestration, and landscape aesthetics [45].…”
Section: Sip10 "Sustainable Grapevine Sector: Payments For Ecosystem ...mentioning
confidence: 99%